A Garden for Childhood. A Comeniana metaphor recreated in our times - Aguirre Lora, Georgina Maria Esther (Historia y Memoria de la Educación, 2019)
The Children’s Garden as such, under the name Kindergarten, was introduced in Mexico as one of the novelties of the Porfirian modernity, and was meant to revert to practices that existed in relation to the instruction of infants. The visit of two Mexican teachers whose purpose was to document the existence of options practiced very successfully in the United States put them in contact with programs, materials and experiences designed by Friedrich Fröbel (1782-1864) that had been widely disseminated in European countries. The purpose of this text is to trace the origins of this institution, the Children’s Garden, beyond the nineteenth century, in a metaphor of the Moravian thinker Juan Amós Comenio (1572-1670) in the context of religious reforms. I have structured the article on three axes: 1) Notes on the contributions of the metaphor as an analytical tool; 2) Regarding the establishment of the Kindergarten as an institution; 3) Juan Amos Comenio and the metaphor of the children’s garden.